On N = 1 4d effective couplings for F-theory and heterotic vacua - Jockers, Hans; Mayr, Peter; Walcher, Johannes (Advances in theoretical and mathematical physics, 2010)
International Press of Boston - publishers of scholarly mathematical and scientific journals and books
Das N ist kursiv geschrieben
Gesehen am 13.02.2018